K-12 and Postsecondary Alignment: Racial/Ethnic Differences in Freshmen Course-taking and Performance at California's Community Colleges - Michal Kurlaender; Matthew Larsen (Arizona State University, 2013)
In this paper we focus on California high school students' transition to community colleges. Our unique dataset tracks five cohorts of California high school juniors into their freshmen year at in-state community colleges. We evaluate the extent to which high school achievement tests (currently not utilized by community colleges in course placement decisions) are useful for predicting academic success at community college. In addition, given persistent disparities in college attainment by race, we explore whether this fundamental relationship between high school achievement, college course-taking, and performance differs for students from different racial/ethnic backgrounds.